Analisis Faktor Risiko Kejadian Malaria di Wilayah Kerja Puskesmas Kuala Bhee Kecamatan Woyla Kabupaten Aceh Barat - Junaidi, Hasrah; Raharjo, Mursid; Setiani, Onny (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2015)
Background: Anual Parasite Incidence (API) in West Aceh in 2010 reached 2.6 per 1000 population, then the API in 2011 decreased 1.05 per 1000 population, in 2012 the API decreased 0.9 per 1000 population, API increased to 0.93 per 1000 in 2013.This research aimed to know the association between environmental, behavioral risk factors and the incidence of malaria in the Working Area of Kuala Bhee Public Health Center in Woyla District.Methods: It was an observationalÂ research using case control design. There were 92 respondents used in this research, consisted of 46 malaria case and 46 controls. Statistical analysis used Chi Square tests, followed by Linear Regresion test.Result: The results showed that variables that become risk factors of incidence malaria: the presence of livestock pens (OR = 2.673, 95% CI = 1.095-6.521), the presence of stagnant water (OR = 4.026, 95% CI = 1.667-9.724), the habit of using mosquito repellent (OR = 3.343, 95% CI = 1.277-8.749), and the habit of activity outside the home at night (OR = 4.724, 95% CI = 1.959-11.389). The mean density of Anopheles 1.9 fish / person / hour with an average Man Bitting Rate (MBR) 13 tail / night and the average Man Hour Density (MHD) 6.9 fish/person/hour. Not found the presence of sporozoites in all samples of the studyConclusion: The presence of cattle sheds around the house, the presence of stagnant water around the house which contained larvae, the habit of using mosquito repellent at night time sleep and customs activity outside the home at night has a probability / risk of contracting malaria possibility of 92%.Â Keywords : malaria, risk factors, environmental, Aceh